Customer satisfaction towards cooperative services: a case study at Koperasi Siswa UiTM Selangor Berhad (KOSISWA) / Muhammad Aiman Mat Yaacob - Mat Yaacob, Muhammad Aiman (2019)
The study discusses about 'Customer Satisfaction towards Cooperative Services: A Case Study at Koperasi Siswa UiTM Selangor Berhad (KOSISWA).' There are many issues and problems arise currently regarding to the services sector. This is because services sector becoming necessity now to the public in doing their daily activities.Without services sector such as mart, supermarket, hotel and other services, human difficult and limited in doing their business. This study focussed on the factors in fluencing customer satisfaction and the level of customer satisfaction towards KOSISWA services which are the objective of this study. This two objective seenvery suitable because meet the criteria that needed. Next, the method that has beenusing in this study is quantitative research. There is literature review section in this study purposes to give some information to the reader about cooperative and customer satisfaction such as definition, legality and opinion of Islamic scholars about cooperative. Research report will be shows after the literature review and will be explain in findings and analysis chapter. Findings and analysis chapter are the main component in this study to explain about the objectives of the study. Lastly, discussion and recommendations will be made about the topic which has been discussed in the study.